Cerebrospinal fluid vasopressin and symptom severity in children with autism. Issue 4 (26th September 2018) - Oztan, Ozge; Garner, Joseph P.; Partap, Sonia; Sherr, Elliott H.; Hardan, Antonio Y.; Farmer, Cristan; Thurm, Audrey; Swedo, Susan E.; Parker, Karen J.
Abstract : Autism is a brain disorder characterized by social impairments. Progress in understanding autism has been hindered by difficulty in obtaining brain‐relevant tissues (eg, cerebrospinal fluid [CSF]) by which to identify markers of disease and targets for treatment. Here, we overcome this barrier by providing evidence that mean CSF concentration of the "social" neuropeptide arginine vasopressin (AVP) is lower in children with autism versus controls. CSF AVP concentration also significantly differentiates individual cases from controls and is associated with greater social symptom severity in children with autism. These findings indicate that AVP may be a promising CSF marker of autism's social deficits. Ann Neurol 2018;84:611–615